The influence of children's fears on adult tolerance. - Potonska, Olga (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
Objective: To confirm the impact of childhood fears on adult tolerance. Methods: questionnaire of the author on the childhood fears; MSTAT-I Tolerance Scale for Ambiguity of Several Types of Incentives; New questionnaire of tolerance for NTN uncertainty. Identified: classification and quantitative parameters of childhood fears; fears of social origin associated with tolerance of uncertainty. It is important to adapt quickly and make non-standard decisions to be successful in today's changing world. One of the main obstacles is the existence of stereotypes – a rigidly stable image of a person's consciousness in terms of objectively existing phenomena makes it possible to perceive the surrounding reality in a convenient form. Сhildhood fears are their basis. Despite this, a need for comprehensive research exists. The importance of the construct of tolerance for uncertainty (from now on referred to as TN) – the ability of a person to accept unknown information, resist the contradictions of information, and overcome conflict and tension arising in a duality situation is extremely increasing in modern psychodiagnostics. The uncertainty tolerant person is described as one who accepts the novelty and uncertainty of situations and can act productively in them. In contrast, the intolerant person is described as one who does not accept the novelty of situations, the world's diversity and is stressed when the possibility of multiple interpretations of stimuli. We view the tolerance of uncertainty as to the opposite of the stereotypical behavior from the psychological perspective. The scope of this publication is to show and substantiate the impact of childhood fears on adult tolerance. Further the development of this issue is important both in the theoretical context – for understanding the dynamism of the mind in the modern changing world, where uncertainty is a common condition for life, and in practical terms – for solving important problems of forming human tolerance social interaction.
Keywords: intolerance; stereotypization; fear; tolerant of imponderability